Offender personality disorder pathway Intensive Intervention Risk Management Service (IIRMS): Barriers to engagement and a vision for the future. (March 2021) - Webster, Nicole; Gardner, Stephanie
As part of the national Offender Personality Disorder (OPD) pathway, Intensive Intervention Risk Management Services are commissioned to offer the opportunity for some eligible offenders to access individualised intervention to support their treatment needs, upon their transition from custody to the community (Skett and Lewis, 2019). However, it has previously been acknowledged that psychological services often fail to reach offenders due to a range of potential psycho-social reasons (Byng et al., 2012; NOMS, 2014; Skett et al., 2017). The current study aims to explore National Probation Service (NPS) and National Health Service (NHS) staff perceptions of the Intensive Intervention Risk Management Service (IIRMS), within the Cumbria, North and South Tyneside regions, including their perception of potential barriers to service delivery. Further, areas of improvement that may overcome potential barriers to engagement are discussed and comparisons are made to barriers identified to engagement within other NHS/NPS partnerships pathways; specifically the Mental Health Treatment Requirement (MHTR) (NOMS, 2014). Results indicate that the IIRMS is useful. However, a number of staff barriers, service user barriers and barriers within the method and delivery of the service were indicated. Results of the study offer the opportunity for shared learning across the pathway and with other services engaging with the most marginalised offenders within our society.